Digitalisasi Sistem Kasir dengan Griyopos pada UMKM Kwetiaw Liang - Candy Candy; Shelvi Shelvi (Lembaga Pengembangan Kinerja Dosen, 2024)
Kwetiaw Liang is a small and medium-sized enterprise (SME) in Batam City engaged in the culinary industry. Based on interview results, it was found that the owner of the SME often experiences difficulties in managing the financial transactions of the business. This community service activity aims to implement a cashier system digitization using Griyopos for more accurate and real-time transaction management, as well as to improve operational performance to be more efficient and effective. Through this activity, it is expected to provide information on the importance of digitizing the financial recording system for the business. The data collection methods used include interviews, observations, and documentation. The results of the community service include automated sales reports, cash flow reports, and profit/loss data. After the implementation process, Kwetiaw Liang SME achieved quite positive results and improved its business performance.